Implementation of Smart City Dimensions to Support Governance in Kubu Raya Regency - Handayani, Dwi Nur; Agussalim, Alfiyah; Alamri, Annisa Rizqa (UIR Press, 2026)
Advances in information and communication technology have been the main driver of the transformation of governance towards the concept of smart cities. The implementation of smart city dimensions is crucial to improving the quality of local government governance. This study analyzes the implementation of smart city dimensions in supporting governance in Kubu Raya Regency. It uses a descriptive qualitative approach. Primary data was obtained through interviews with the Communication and Information Agency and the Regional Development Planning Agency, while secondary data was obtained from various related documents. Qualitative data analysis shows that Kubu Raya Regency is gradually implementing the dimensions of a smart city, starting with a focus on smart governance and various innovations within it. Meanwhile, other dimensions of the smart economy and smart people include several initiatives such as “SIAP PAK” and Cash System Management non-cash payments in the economic sector, and digital literacy programs in the education sector. The smart environment includes plans for renewable energy programs and technology-based waste management. Smart mobility is geared toward public transportation development plans and electric vehicle support. Smart living, telemedicine services, and technology-based public safety are planned to improve the quality of life for the community. Although the smart city dimension has not been fully implemented, Kubu Raya Regency has established ctionn plan for the implementation of the smart city dimension.